Pengembangan Media Membaca Berbasis Android “Si Tepat” Pada Mapel Bahasa Indonesia Kelas I SD - Joko Ebib Usantoro; Rofian; Lina Putriyanti (DIKDAS MATAPPA: Jurnal Ilmu Pendidikan Dasar, 2024)
The research aims to determine the development of Android-based media "SI TEPAT" that can be used as an interesting learning media in elementary schools. The research method used is research and development using the Sugiyono model with several steps, namely: potential and problems, data collection, product design, design validation, design revision, and field trials. The population and samples taken were grade 1 students at 3 elementary schools in Wonoboyo District consisting of Wates State Elementary School, Kebonsari 2 Elementary School, and Semen State Elementary School. The research results show that the Android-based application SI TEPAT is very effective as a learning medium. The results obtained from the test results carried out on teachers and students showed that the teacher response was 96.33% or very appropriate and the student response was 87.61% or very appropriate. The benefits of Android-based media "SI TEPAT" can be used as a learning medium to help make it easier for students to learn Indonesian starting reading material.